2007
DOI: 10.1111/j.1462-5822.2007.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Rab11B small GTPase regulates secretion of cysteine proteases in the enteric protozoan parasiteEntamoeba histolytica

Abstract: SummaryVesicular trafficking plays a pivotal role in the virulence of the enteric protozoan parasite Entamoeba histolytica. In the present study, we showed that one isotype of the small GTPase Rab11, EhRab11B, plays a central role in the secretion of a major virulence factor, cysteine proteases. EhRab11B did not colocalize with markers for the endoplasmic reticulum, early endosomes and lysosomes, but was partially associated with non-acidified vesicles in the endocytic pathway, likely recycling endosomes. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 69 publications
(97 reference statements)
1
73
1
Order By: Relevance
“…Although the protein was not expressed in a soluble form, a relatively high level of expression (average 47 mg/liter of culture) was achieved in BL21 Codon Plus (DE3) RIPL (Stratagene) cells as inclusion bodies. Although existing refolding methods of EhCPs (16,17,38) failed to solubilize and recover active EhCP4, a refolding system that was modified from conditions used to refold Falcipain-2 (22) successfully produced active enzyme. Like other papain family cysteine proteinases (39), EhCP4 underwent autocatalytic activation in buffers containing 5 mM reducing reagent (e.g.…”
Section: Expression Andmentioning
confidence: 99%
“…Although the protein was not expressed in a soluble form, a relatively high level of expression (average 47 mg/liter of culture) was achieved in BL21 Codon Plus (DE3) RIPL (Stratagene) cells as inclusion bodies. Although existing refolding methods of EhCPs (16,17,38) failed to solubilize and recover active EhCP4, a refolding system that was modified from conditions used to refold Falcipain-2 (22) successfully produced active enzyme. Like other papain family cysteine proteinases (39), EhCP4 underwent autocatalytic activation in buffers containing 5 mM reducing reagent (e.g.…”
Section: Expression Andmentioning
confidence: 99%
“…We had previously shown that EhCP1, EhCP2, and EhCP5 are passively released during phagocytosis (17). This release is likely to be part of the newly described EhRab11B-associated secretory pathway, as overexpression of EhRab11B led to increased release of all three proteinases (30).…”
mentioning
confidence: 99%
“…Overexpression of this gene led to increased cysteine protease [ 76 ], Majumder and Lohia [ 77 ] and Bosch et al [ 78 ] and cytolytic activities. Overexpression of Rab11B is also associated with enhanced exocytosis, which indicates its involvement in recycling of endosomes [ 81 ]. Moreover, Rab7 has nine members, of which Rab7A and Rab7B display distinct localization in trophozoites.…”
Section: Phagosome Maturationmentioning
confidence: 99%